Decoupling of a 3D-force flexible tactile sensor. Issue 1 (March 2021) - Li, S; Zhang, Y; Meng, F; Chu, Z; Pan, H
Abstract: Due to the frame structure of the three-dimensional force sensor which is made of pressure-sensitive conductive rubber, its output data is coupled seriously. To solve this issue, the force-applied model of the sensor is established based on the wire resistance model, which provides a theoretical basis for sensor dimensionality reduction and decoupling. In this paper, the Cartesian coordinate system is established to realize the judgment of the direction of the three-dimensional force applied on the senor, and the sensor output data is decoupled using the least square method. According to the experiment result, the measurement error of the sensor is small and the decoupling method is proved to be suitable.